2014
DOI: 10.1002/cbic.201402051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Reactivity of Carbohydrate Photoaffinity Probes with Different Photoreactive Groups

Abstract: A judicious choice of photoreactive group is critical in successful photoaffinity labeling studies of small molecule-protein interactions. A set of carbohydrate-based photoaffinity probes was prepared to compare the effects of three major photoreactive groups on the efficiency and selectivity of crosslinking a binding protein with low affinity. We showed that, despite the low crosslinking yield, the diazirine probe displayed the high ligand-dependent reactivity consistent with the ideal mechanism of photoaffin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 38 publications
4
59
0
Order By: Relevance
“…5,5-Azo-hexanoic acid (120 mg, 0.845 mmol) 11,15 , and N-hydroxysuccinimide (NHS; 102 mg, 0.887 mmol) was dissolved in dry CH 2 Cl 2 (2.56 mL), and added EDCI (138 mg, 0.887 mmol) at 0°C, which was stirred at 0°C for 10 min, then at room temperature for 1 h. The reaction mixture was diluted with CH 2 Cl 2 and washed with 10% NH 4 Cl three times. The organic layer was dried over Na 2 SO 4 then concentrated in vacuo to give 9 as white solid.…”
Section: Compoundmentioning
confidence: 99%
See 1 more Smart Citation
“…5,5-Azo-hexanoic acid (120 mg, 0.845 mmol) 11,15 , and N-hydroxysuccinimide (NHS; 102 mg, 0.887 mmol) was dissolved in dry CH 2 Cl 2 (2.56 mL), and added EDCI (138 mg, 0.887 mmol) at 0°C, which was stirred at 0°C for 10 min, then at room temperature for 1 h. The reaction mixture was diluted with CH 2 Cl 2 and washed with 10% NH 4 Cl three times. The organic layer was dried over Na 2 SO 4 then concentrated in vacuo to give 9 as white solid.…”
Section: Compoundmentioning
confidence: 99%
“…1). 11 For the synthesis of 1 and 2, N-Boc-Lys (Fmoc)-OH was first derivatized with an alkyne tag by amide coupling of propargyl amine then the benzophenone group or aryl azide groups was introduced to 7 by acylation at the e-amine with an N-hydroxysuccinimide (NHS)-ester after deprotection of the Fmoc group (Scheme 2). Lactosyl azide was derivatized with a carboxylic acid linker via copper-promoted azide-alkyne cycloaddition (CUAAC), which was then coupled to 4 and 5 using COMU to furnish benzophenone probe 1 and aryl azide probe 2, respectively.…”
Section: Synthesis Of Carbohydrate Photoaffinity Probesmentioning
confidence: 99%
“…Overall, these experiments demonstrated that DA-based glycolipid photo-affinity probes are more suitable than BP-based probes to explore specific glycolipid binding proteins. The researchers [101] also compared the reactivity of carbohydrate PAL probes with different photoreactive groups (Fig. 35 Right).…”
Section: Comparative Probesmentioning
confidence: 99%
“…3 In the cases with low-affinity carbohydrate-binding proteins, there is an additional difficulty that the reaction conditions with high concentration of photoaffinity probes is required to ensure maximum binding and this often leads to increased nonselective crosslinking of abundant proteins. 11 The AuNP-based photoaffinity probes therefore, should help address these issues by increasing the selectivity of PAL through affinity enhancement and by efficiently removing the nonspecifically bound proteins using a stringent washing procedure.…”
Section: Introductionmentioning
confidence: 99%